Characterization of polyhydroxyalkanoate blends incorporating unpurified biosustainably produced poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate). Issue 2 (8th July 2015) - Martínez‐Abad, Antonio; Cabedo, Luis; Oliveira, Catarina S. S.; Hilliou, Loic; Reis, Maria; Lagarón, José María; Lagarón, José M.; López‐Rubio, Amparo; Fabra, María José
ABSTRACT Poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) (PHBV) produced by mixed bacterial cultures derived from a cheese whey (CW) industrial by‐product (unpurified PHBV; u‐PHBV) was incorporated into commercial PHBV without previous purification or isolation processes. The presence of certain impurities was evident as investigated by scanning electron microscopy. The crystallinity of the polymer fraction was decreased by about 3% compared to the commercial PHBV. The onset of thermal degradation was not substantially affected by the incorporation of the u‐PHBV fraction. A higher flexibility and elongation at break was mostly attributed to the increased contents in 3‐hydroxyvalerate in the blends with increasing u‐PHBV content. Water and D‐limonene vapor permeability were not affected up to u‐PHBV contents of 15 wt %. This study puts forth the potential use of unpurified PHBV obtained from mixed microbial cultures and grown from industrial by‐products as a cost‐effective additive to develop more affordable and waste valorized packaging articles. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 42633.